2020
DOI: 10.1186/s40478-020-00967-w
|View full text |Cite
|
Sign up to set email alerts
|

Tau Ser208 phosphorylation promotes aggregation and reveals neuropathologic diversity in Alzheimer’s disease and other tauopathies

Abstract: Tau protein abnormally aggregates in tauopathies, a diverse group of neurologic diseases that includes Alzheimer's disease (AD). In early stages of disease, tau becomes hyperphosphorylated and mislocalized, which can contribute to its aggregation and toxicity. We demonstrate that tau phosphorylation at Ser208 (pSer208) promotes microtubule dysfunction and tau aggregation in cultured cells. Comparative assessment of the epitopes recognized by antibodies AT8, CP13, and 7F2 demonstrates that CP13 and 7F2 are spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 86 publications
1
69
0
Order By: Relevance
“…We have not observed any long tangles in any of the samples, which is connected with performing a sonication step of the material prior to injection into mice brains. In addition, we performed immunohistochemistry analysis of frontal cortices from the control and CBD cases using CP13 antibody ( Supplementary Figures 1D,F ) specific for tau phosphorylated at Ser202 (pSer202), commonly used to detect tau pathology in both early (pretangle) and more advanced stages of neurofibrillary tangle accumulation ( 22 24 ). The CP13 positive (CP13 + ) astrocytic plaques were observed only in the CBD case.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have not observed any long tangles in any of the samples, which is connected with performing a sonication step of the material prior to injection into mice brains. In addition, we performed immunohistochemistry analysis of frontal cortices from the control and CBD cases using CP13 antibody ( Supplementary Figures 1D,F ) specific for tau phosphorylated at Ser202 (pSer202), commonly used to detect tau pathology in both early (pretangle) and more advanced stages of neurofibrillary tangle accumulation ( 22 24 ). The CP13 positive (CP13 + ) astrocytic plaques were observed only in the CBD case.…”
Section: Resultsmentioning
confidence: 99%
“…The hTau mice overexpress all six human tau isoforms under the tau promoter in the murine tau KO background. Next, we examined tau pathology at 1 and 12 months post-surgery using CP13 antibody (pSer202, pretangles, and more advanced stages of neurofibrillary tangle accumulation) ( 22 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that the AT8 binding motif does not only include the well-known pS202/pT205 epitope but also pS208 which is important for the affinity and kinetics of AT8 binding (Malia et al, 2016 ). Since phosphorylation of S208 was suggested to enhance the formation of tau filaments that lead to NFTs (Xia et al, 2020 ), PP2Ac likely controls early hyperphosphorylation steps in tau pathogenesis that promote aggregation but are still reversible. There is also evidence from a mouse model expressing a repressible human tau variant, that the pathological processes responsible for cognitive decline and the processes underlying NFT-formation may dissociate at a certain stage of Tau pathology (SantaCruz et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…The observation that tau aggregates are hyperphosphorylated [ 49 ] indicates that this post-translational modification plays an important role in this process [ 63 , 64 ]. In this regard, it has recently been shown that specific tau phosphorylation at Ser208 promotes the aggregation of the protein, whereas phosphorylation at Ser202 and Thr205 leads to its mislocalization to the soma and dendrites [ 65 ]. However, phosphorylation at specific sites can suppress aggregate formation [ 66 ].…”
Section: Tau Proteinmentioning
confidence: 99%